THE IMPACT OF SOCIAL MEDIA ON CHILDREN'S SOCIAL EMOTIONAL DEVELOPMENT - Nurwinda Saputri; Hairuddin Cikka; Rizki Amalia Sholihah (Adisam Publisher, 2024)
Modern life is greatly impacted by social media, both favorably and unfavorably. Social media is a key element in managing reputation and business growth in the digital era. Using social media for business can encourage development effectively and efficiently. However, social media also has negative aspects, such as important debates around cyber safety and the dangers to children who frequently use social media. Children's social The capacity of a youngster to completely regulate and express their emotions is known as emotional development, both positive and negative. Three factors can affect how a child develops socially and emotionally, namely heredity, environmental factors and general factors. Social media has a significant impact on children's social and emotional development, both positive and negative. The advantages and disadvantages consist of increased social connectedness, learning and creativity, opportunities to share thoughts and feelings, disruption to mental health, dependency and concentration problems, and the influence of unhealthy content. This research uses library research methods. The concept and significance of children's social emotional development, the evolution of social media, and the advantages and disadvantages of social media use for kids' social emotional development are all covered in this study.